Effect of the initiator type in the styrene polymerization - González, Ida; Oliva, Haydée (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this work bulk styrene polymerization using mixtures of monofunctional and bifunctional initiators and non isothermal conditions was studied. The effect of global concentration and mixture composition on the reaction rate and the distribution of the molecular weight of the synthesized polymer were analyzed. The use of bifunctional initiators permits to reduction of the reaction cycle without appreciably modifying the molecular weight distribution in comparison with the polyrnerization using mixtures of monofunctional initiators.